Association of Prepregnancy Nutritional Status and Physical Activity Levels with Birth Size Outcomes among West Sumatran Pregnant Women: Results from the Vitamin D Pregnant Mothers Cohort Study in Indonesia - Aji, Arif Sabta; Yusrawati, Yusrawati; Malik, Safarina G.; Kusuma, Chahya; Lipoeto, Nurindrawaty (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Maternal and neonatal morbidity is still high in developing countries like in Indonesia. There are several factors may affect maternal health during pregnancy such as physical activity level (PAL) and pre-pregnancy nutritional status. Aim: To analyze the association between maternal physical activity status (PAL) and pre-pregnancy body mass index (PP BMI) with birth size outcomes. Methods: A prospective birth cohort study, Vitamin D Pregnant Mothers (VDPM) Study, to 183 healthy singleton pregnant women. Pre-pregnancy body mass index was classified according to WHO guidelines for Asian Population. Women PAL was measured at the first trimester (T1) and third trimester (T3) during pregnancy using the Global Physical Activity Questionnaire (GPAQ). Birth size outcomes were measured immediately after birth such as birth weight, birth length, and head circumference. Results: Pregnant women at T3 had two times lower physical activity than T1 of pregnancy (OR, 2.18; CI, 1.044-4.57; p = 0.045). Maternal PAL at T1 and T3 were mostly in sedentary level (74.3% and 77.1%, respectively). There was no association between PP BMI, PAL, and birth size outcomes (p > 0.05 for all comparisons). However, the physical activity at T1 had a significant association with birth weight outcomes [MD (95%CI): 155.3 (13.8 – 296.8), p = 0.032]. There was a significant interaction between maternal PAL and PP BMI on birth weight (p interaction = 0.011) and head circumference (p interaction = 0.034). Conclusions: Our study reveals that pre-maternal nutritional status and physical activity behavior during the pregnancy associated with the head circumference and birth weight outcomes. Further large studies are needed to confirm our findings.